2021
DOI: 10.1038/s41467-021-21212-5
|View full text |Cite
|
Sign up to set email alerts
|

Social networks predict the life and death of honey bees

Abstract: In complex societies, individuals’ roles are reflected by interactions with other conspecifics. Honey bees (Apis mellifera) generally change tasks as they age, but developmental trajectories of individuals can vary drastically due to physiological and environmental factors. We introduce a succinct descriptor of an individual’s social network that can be obtained without interfering with the colony. This ‘network age’ accurately predicts task allocation, survival, activity patterns, and future behavior. We anal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 93 publications
4
73
0
Order By: Relevance
“…The differences described by life-PCA component 2 agree with recent work which found differences among individual bees in developmental trajectories, as described in the age at which they change interactions patterns and nest substrate usage (Wild et al, 2021). Moreover, Wild et al (2021) found that developmental trajectories began to significantly diverge at approximately six-days of age.…”
Section: Behavioral Clustering Of Bee-livessupporting
confidence: 86%
See 3 more Smart Citations
“…The differences described by life-PCA component 2 agree with recent work which found differences among individual bees in developmental trajectories, as described in the age at which they change interactions patterns and nest substrate usage (Wild et al, 2021). Moreover, Wild et al (2021) found that developmental trajectories began to significantly diverge at approximately six-days of age.…”
Section: Behavioral Clustering Of Bee-livessupporting
confidence: 86%
“…Using the BeesBook system, the raw image data were processed to detect and decode the individually marked bees (Boenisch et al, 2018;Wild et al, 2018Wild et al, , 2021. For each individual, its tag id, id detection confidence, position, and orientation were tracked over time, and stored in a PostgreSQL database.…”
Section: Data Processing and Quantities To Describe Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…Throughout ontogenesis, worker ants or bees change from one caste to another 21 . This is associated with age-related cognitive decline 22 and changes in their social capital; they no longer interact with the same individuals [23][24][25] .…”
Section: Social Capital Changes With Chronological Agementioning
confidence: 99%